Franchising in Ethiopianá¡ The Need for Regulation - Zergaw, Tegegne (Bahir Dar University Journal of Law, 2023)
Franchising is a way of doing business in which the franchisor licenses its known business model or trademark for the use of the franchisee in return for consideration. It becomes a viable solution for business startups, especially for small and medium enterprises (SME), and to penetrate the foreign market. Franchising benefits not only those parties involved in the business but also the national economy. In order to create a leveling field and protect the interests of parties countries are on the move for regulating franchising. This article assesses the regulation of franchising in Ethiopia using comparative analysis method. Even though there are scattered laws pertaining to franchising, still the country lacks, compared to other countries, comprehensive and detailed laws on franchise regulation. The research identified several legal gaps in regulating franchising; essential aspects of franchising such as, precontractual disclosure, parties’ relationship, and registration are not regulated in a comprehensive manner. Hence, the author recommends the adoption of comprehensive franchise laws that take into consideration the best international practice.